Midturbinate Swabs Are Comparable to Nasopharyngeal Swabs for Quantitative Detection of Respiratory Syncytial Virus in Infants. (21st November 2018) - Blaschke, Anne J; McKevitt, Matt; Ampofo, Krow; Lewis, Tammi; Chai, Hao; Guo, Ying; Dorsch, Julianna; Vanderhoof, Erin; Rosen, Priscilla; Freimann, Volker; Korgenski, E Kent; Toback, Seth; et al.
Abstract: Nasopharyngeal (NP) swabs are generally used to detect respiratory syncytial virus (RSV) in infants. However, midturbinate (MT) swabs may provide comparable results. In this study, we enrolled hospitalized infants aged <24 months with RSV and collected NP and MT swabs. The resulting viral loads measured by real-time reverse-transcription quantitative polymerase chain reaction were similar. Most parents preferred MT swabs over NP swabs.